1991
DOI: 10.1172/jci115346
|View full text |Cite
|
Sign up to set email alerts
|

The effects of infusion of insulinlike growth factor (IGF) I, IGF-II, and insulin on glucose and protein metabolism in fasted lambs.

Abstract: In vivo effects of 300-min infusions of recombinant insulinlike growth factor I (IGF-I) and IGF-II on glucose and protein metabolism have been investigated in awake, fasted lambs. Two doses of recombinant human (rh) IGF-I were infused: 6.7 nmol/ kg * h, which induced hypoglycemia, and 2.0 nmol/kg. h, which did not. The effects were compared with an insulin infusion (0.17 nmol/kg -h) that had the same hypoglycemic potential as the high dose rhIGF-I infusion. rhIGF-II was infused at a rate of 6.7 nmol/kg -h. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 42 publications
7
69
1
Order By: Relevance
“…In both studies, this important stimulus of nutrient intake was evident in the increased circulating IGF-I during the 24-h period in all feeding groups. Few studies have measured a specific effect of IGF-I on protein synthesis in neonatal animals, although administration of IGF-I has been shown to increase muscle protein synthesis in young growing animals (10,11). Recently, we have demonstrated that chronic administration of IGF-I to neonatal pigs via osmotic pumps resulted in a modest increase in skeletal muscle, but not visceral organ protein synthesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, this important stimulus of nutrient intake was evident in the increased circulating IGF-I during the 24-h period in all feeding groups. Few studies have measured a specific effect of IGF-I on protein synthesis in neonatal animals, although administration of IGF-I has been shown to increase muscle protein synthesis in young growing animals (10,11). Recently, we have demonstrated that chronic administration of IGF-I to neonatal pigs via osmotic pumps resulted in a modest increase in skeletal muscle, but not visceral organ protein synthesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…In other IGF-II-transgenic mouse models increased levels of IGFBP-2 (Rogler et al 1994, Wolf et al 1994, IGFBP-1 and IGFBP-5 have been noted (Rogler et al 1994). A drop in the serum level of IGF-I has often been observed after IGF-II administration or IGF-II overproduction (Douglas et al 1991, Koea et al 1992, Rogler et al 1994, Conlon et al 1995, Wolf et al 1995. The reduction in serum IGF-I is most likely due to displacement of IGF-I from the binding proteins in the presence of high concentrations of IGF-II (Blackburn et al 1997).…”
Section: Dexamethasone In Igf-ii-transgenic Mice 路 R Rooman and Othermentioning
confidence: 99%
“…On the basis of the observation that co-infusion of IGF-II with IGF-I blocked the anti-catabolic effect of IGF-I in sheep (25), it has been speculated that IGF-II may be a functional inhibitor of IGF-I, representing a mechanism that prevents overgrowth and hyperanabolism (6). Another feature compatible with this hypothesis is the consistently observed decrease in serum IGF-I after administration of IGF-II to pituitary-sufficient animals (14) and in patients (26) or experimental animals (15) …”
Section: Discussionmentioning
confidence: 99%
“…13). Specifically, this approach aimed at elucidating the mechanism of the decrease in serum IGF-I concentrations that is a consistent feature of in vivo studies involving administration of IGF-II to pituitary-sufficient animals (14) or transplantation of IGF-II-secreting tumours to nude rodents (15).…”
Section: Introductionmentioning
confidence: 99%